Europe's third way in cyberspace: What part does the new EU Cybersecurity Act play? - Annegret Bendiek; Martin Schallbruch (Stiftung Wissenschaft und Politik (SWP), 2019)
Cybersecurity has become a key issue for Europe in the global digital transformation. The EU Cybersecurity Act lays down a legal framework whose aim is to achieve global reach. Embedded in a policy that combines digital sovereignty with strategic interdependence, the Act could represent the gateway to a third European pathway in cyberspace, something in between the US model of a liberal market economy and the Chinese model of authoritarian state capitalism. The Cybersecurity Act will be a binding framework for action and provide a tailwind for German cybersecurity policy.
Keywords: 320